Usp14 deficiency increases tau phosphorylation without altering tau degradation or causing tau-dependent deficits. - Youngnam N Jin; Ping-Chung Chen; Jennifer A Watson; Brandon J Walters; Scott E Phillips; Karen Green; Robert Schmidt; Julie A Wilson; Gail V Johnson; Erik D Roberson; Lynn E Dobrunz; Scott M Wilson (PLoS ONE, 2012)
Regulated protein degradation by the proteasome plays an essential role in the enhancement and suppression of signaling pathways in the nervous system. Proteasome-associated factors are pivotal in ensuring appropriate protein degradation, and we have previously demonstrated that alterations in one of these factors, the proteasomal deubiquitinating enzyme ubiquitin-specific protease 14 (Usp14), can lead to proteasome dysfunction and neurological disease. Recent studies in cell culture have shown that Usp14 can also stabilize the expression of over-expressed, disease-associated proteins such as tau and ataxin-3. Using Usp14-deficient ax(J) mice, we investigated if loss of Usp14 results in decreased levels of endogenous tau and ataxin-3 in the nervous system of mice. Although loss of Usp14 did not alter the overall neuronal levels of tau and ataxin-3, we found increased levels of phosphorylated tau that correlated with the onset of axonal varicosities in the Usp14-deficient mice. These changes in tau phosphorylation were accompanied by increased levels of activated phospho-Akt, phosphorylated MAPKs, and inactivated phospho-GSK3β. However, genetic ablation of tau did not alter any of the neurological deficits in the Usp14-deficient mice, demonstrating that increased levels of phosphorylated tau do not necessarily lead to neurological disease. Due to the widespread activation of intracellular signaling pathways induced by the loss of Usp14, a better understanding of the cellular pathways regulated by the proteasome is required before effective proteasomal-based therapies can be used to treat chronic neurological diseases.